(untitled) (Semiárida, 2020)
Plant galls are abnormal growths in plant organs caused by inducing organisms such as bacteria, fungi or metazoans. On the leaves of “chañar”, Geoffroea decorticans (Gill. ex Hook. et Arn.) Burkart, eryiophyid mites induce galls. The aim of this work was to describe morpho-anatomical and histochemical aspects of the mature mite gall and identify the inducer. The galls were collected during 2015-2016 in Santa Rosa and Anguil (La Pampa, Argentina). Anatomical and histochemical analysis of gall-free and galled leaves was performed. The leaf structure without gall is isolateral with scarce spongy parenchyma between both palisade parenchymas. The studied gall is sac-shaped extending into a thin neck with an ostiole, the gall projects to both foliar surfaces and it is unilocular. Externally, the gall is covered by the epidermis (adaxial and abaxial) and hypodermis. The gall body is composed of photosynthetic parenchyma and tanniferous sheath. The gall chamber is covered internally by the nutritional tissue. The parenchyma, mainly spongy one is the tissue that exhibits the most relevant changes. The studied mite gall is induced by a species of the genus Aceria (Eriophyidae). A tarsonemid mite is reported as gall associated fauna.